Low dose LPS does not increase TLR4 expression on monocytes in a human in vivo model - Lichte, Philipp; Grigoleit, Jan-Sebastian; Steiner, Eva Maria; Kullmann, Jennifer S.; Schedlowski, Manfred; Oberbeck, Reiner; Kobbe, Philipp (Cytokine (Philadelphia, Pa.), 2013)
•In vivo administration of 0.4ng/kg LPS causes a significant inflammatory response.•Administration of 0.4ng/kg LPS induces CD11b expression on monocytes in human.•Administration of 0.4ng/kg LPS does not change TLR4 expression on monocytes. Toll like receptor 4 (TLR4) is the major recognition receptor for lipopolysaccharides and plays a major role in the inflammatory response. CD11b is expressed on the surface of many leukocytes including monocytes. The CD11b/CD18 complex is involved in the inflammatory response by mediating migration and adhesion of leukocytes. The aim of this human in vivo study was to investigate the expression of TLR4 and CD11b on the surface of human monocytes after in vivo low-dose LPS stimulation. We performed a double-blind, randomized crossover study with 16 healthy males who received a bolus injection of bacterial lipopolysaccharide (LPS; 0.4ng/kg) or normal saline. Vital parameters, blood counts, serum cytokine levels, the expression of TLR4, and CD11b on CD14 positive cells were analyzed. The experimentally induced inflammatory response was reflected by transient increases in body temperature, circulating leukocyte numbers, and plasma levels of pro- (TNF-α, IL-6) and anti-inflammatory cytokines (IL-10, IL-1ra). In contrast to a significant increase in CD11b expression, no changes in TLR4 expression on circulating monocytes were detectable. Early changes in TLR4 expression on circulating monocytes are not necessarily part of the inflammatory response to low dose LPS in humans whereas the detected increase of CD11b expression might already be sufficient for optimized recognition and signalling.